2021
DOI: 10.3389/fimmu.2021.724934
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diagnostic Signatures and Immune Cell Infiltration Characteristics in Rheumatoid Arthritis by Integrating Bioinformatic Analysis and Machine-Learning Strategies

Abstract: BackgroundRheumatoid arthritis (RA) refers to an autoimmune rheumatic disease that imposes a huge burden on patients and society. Early RA diagnosis is critical to preventing disease progression and selecting optimal therapeutic strategies more effectively. In the present study, the aim was at examining RA’s diagnostic signatures and the effect of immune cell infiltration in this pathology.MethodsGene Expression Omnibus (GEO) database provided three datasets of gene expressions. Firstly, this study adopted R s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 48 publications
0
24
1
Order By: Relevance
“…We only found significant differences in the ratio CD8 TEM GNLY to CD8 Naïve between patients with ASS-ILD and HDs. Current researches have reported the correlations between GNLY or CD8 T cells and several autoimmune diseases, such as differential expressions of GNLY in rheumatic arthritis and healthy state, an association of GNLY expressions in CD8 cells and steroid resistance in polymyositis, an association of disease flares and proportions of activated CD8 T cells in systemic lupus erythematosus (32)(33)(34). Our study showed that CD8 T cells in the blood of patients with ASS-ILD were skewed towards an activated phenotype characterized by high expression of GNLY.…”
Section: Discussionmentioning
confidence: 99%
“…We only found significant differences in the ratio CD8 TEM GNLY to CD8 Naïve between patients with ASS-ILD and HDs. Current researches have reported the correlations between GNLY or CD8 T cells and several autoimmune diseases, such as differential expressions of GNLY in rheumatic arthritis and healthy state, an association of GNLY expressions in CD8 cells and steroid resistance in polymyositis, an association of disease flares and proportions of activated CD8 T cells in systemic lupus erythematosus (32)(33)(34). Our study showed that CD8 T cells in the blood of patients with ASS-ILD were skewed towards an activated phenotype characterized by high expression of GNLY.…”
Section: Discussionmentioning
confidence: 99%
“…The synovial tissue is of interest for gene analysis in RA. In several previous studies on RA, bioinformatic analyses have been performed with the following research objectives: identifying key genes for diagnosis [ 26 33 ], immune infiltration [ 28 , 31 33 ], and therapeutic targets [ 26 , 32 ]; however, the sample size of these studies was not very large, and the research content that integrates these three research objectives is lacking. Therefore, various bioinformatic tools were used in this study to analyse differentially expressed gene (DEG) data between patients with RA and healthy individuals from the comprehensive gene expression database [ 34 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…GNLY is a cytotoxic granular protein secreted by cytotoxic T lymphocytes and NK cells 45 that exerts toxic effect on bacteria, fungi, parasites, and tumors 46 , GNLY acts as an immune alarmin and promotes antigen-presenting cell activation through TLR4 47 . GNLY is associated with the efficacy of pegylated-interferon-alpha therapy in Chinese patients with HBeAg-positive chronic hepatitis 48 , rheumatoid arthritis 49 , and Mycoplasma pneumoniae pneumonia 50 . IL2RB, a subunit of IL-2R, mediates signal transduction for IL-2R and IL-15R 51 , Mutations in human IL2RB result in immune dysregulation, cytomegalovirus (CMV) susceptibility 52 , reduced T reg frequency, and an abnormal NK compartment 53 .…”
Section: Discussionmentioning
confidence: 99%